Different Starting Points for English Language Learning: A Comparative Study of Danish and Spanish Young Learners. Issue 4 (8th August 2018) - Muñoz, Carmen; Cadierno, Teresa; Casas, Isabel
Abstract: This study compared receptive English grammar skills of two groups of 7‐ and 9‐year‐old Danish children at the beginning of second language (L2) instruction in English, and two groups of Spanish/Catalan children of the same age after several years of instruction. The study examined the influence of two language‐related factors (receptive vocabulary skills, cognate linguistic distance) and two context‐related factors (amount of formal instruction, frequency of exposure to English outside school), additionally focusing on the gender variable. Results revealed that the amount of formal instruction had a lesser role in the children's receptive grammar knowledge than cognate linguistic distance and out‐of‐school contact with English (particularly with audiovisual material). These factors may explain why Danish children's receptive knowledge of English prior to school instruction is largely similar to that of Spanish children after several years of instruction, revealing a sharp contrast in their respective starting points for L2 learning.